2018
DOI: 10.1530/rep-18-0140
|View full text |Cite
|
Sign up to set email alerts
|

IRF5 is increased in labouring myometrium and regulates pro-labour mediators

Abstract: Preterm birth continues to be the leading cause of neonatal mortality and morbidities that can extend into adult life. Few treatment options stem from our incomplete understanding of the mechanisms of human labour and delivery. Activation of the inflammatory response in gestational tissues by inflammation and/or infection leads to the production of pro-inflammatory and pro-labour mediators, thus preterm birth. Interferon regulatory factor 5 (IRF5) has recently emerged as an important pro-inflammatory transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…It has also been reported that the suppressed IRF5 production under normoxic conditions modulated (suppressed) the production of other pro-in ammatory cytokines [29]. Furthermow, it has been shown that IRF5 plays a role in the regulation of in ammatory response in myometrium and that the IRF5 expression level increases in the myometrium with labor [13]. Study has shown that gene polymorphisms occurring in IRF5 were associated with recurrent spontaneous abortions [14].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It has also been reported that the suppressed IRF5 production under normoxic conditions modulated (suppressed) the production of other pro-in ammatory cytokines [29]. Furthermow, it has been shown that IRF5 plays a role in the regulation of in ammatory response in myometrium and that the IRF5 expression level increases in the myometrium with labor [13]. Study has shown that gene polymorphisms occurring in IRF5 were associated with recurrent spontaneous abortions [14].…”
Section: Discussionmentioning
confidence: 96%
“…IRF5, which is a from this IRF family, induces the production of many in ammatory molecules involved in the pathogenesis of autoimmune diseases [11,12]. It has been shown that IRF5 level increases in the myometrium with labor, and gene polymorphisms are associated with recurrent spontaneous abortions [13,14]. It has also been reported that IRF5 plays a role in the "cytokine storm" seen in some infections such as COVID-19 [15].…”
Section: Introductionmentioning
confidence: 99%